ANALISIS TINGKAT UTILITY TERHADAP LAYANAN APLIKASI BSI MOBILE DI KOTA BANDA ACEH - Noviandri Yudistira; Apridar Apridar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2023)
AbstractThis study aims to analyze the utility level of BSI Mobile application services in Banda Aceh City. This study uses a quantitative descriptive analysis. The population of this study were customers of Bank Syariah Indonesia (BSI) in Banda Aceh City with a sample size of 84 customers using snowball sampling. This study uses a multiple linear regression analysis model to analyze the utility level of BSI Mobile application services in Banda Aceh City with the variables of efficiency, convenience and security. The results of this study indicate that the variable efficiency of use, variable comfort and security variables simultaneously have a positive and significant influence on the utility level of BSI Mobile services in the city of Banda Aceh. It is hoped that Bank Syariah Indonesia (BSI) can redevelop the BSI Mobile application with service and security features so that customers can more easily and of course feel safe when using the BSI Mobile application.Keywords: Utility, Efficiency of Use, Security, Convenience, Internet Banking.